2011
DOI: 10.1073/pnas.1103195108
|View full text |Cite
|
Sign up to set email alerts
|

Female extrapair mating behavior can evolve via indirect selection on males

Abstract: In many species that form socially monogamous pair bonds, a considerable proportion of the offspring is sired by extrapair males. This observation has remained a puzzle for evolutionary biologists: although mating outside the pair bond can obviously increase the offspring production of males, the benefits of such behavior to females are less clear, yet females are known to actively solicit extrapair copulations. For more than two decades adaptionist explanations have dominated the discussions, yet remain contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
194
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(209 citation statements)
references
References 57 publications
11
194
2
1
Order By: Relevance
“…An interesting evolutionary implication of this sex difference is that the plastic sex (females) might become more shielded from genetic evolution of mate preferences than the less plastic sex (males) [13], a prediction that should be investigated in future quantitative genetic and selection studies in this area. A recent study on sex-specific mate preferences in birds found evidence for an evolutionary constraint in the form of an intersexual genetic correlation and shared inheritance of mating behaviours of males and females [51]. By contrast, another recent study on the fruit fly Drosophila serrata found no evidence of a genetic correlation between male and female mate preferences, strongly suggesting that in this insect, different sets of loci govern male and female mate preferences [52].…”
Section: Discussionmentioning
confidence: 88%
“…An interesting evolutionary implication of this sex difference is that the plastic sex (females) might become more shielded from genetic evolution of mate preferences than the less plastic sex (males) [13], a prediction that should be investigated in future quantitative genetic and selection studies in this area. A recent study on sex-specific mate preferences in birds found evidence for an evolutionary constraint in the form of an intersexual genetic correlation and shared inheritance of mating behaviours of males and females [51]. By contrast, another recent study on the fruit fly Drosophila serrata found no evidence of a genetic correlation between male and female mate preferences, strongly suggesting that in this insect, different sets of loci govern male and female mate preferences [52].…”
Section: Discussionmentioning
confidence: 88%
“…This may indicate that there is no additive genetic variation for extra-pair mating by females, either as a result of strong past selection, or because extra-pair matings are initiated opportunistically by males. Similarly, the fact that extrapair fathers are not more likely to have daughters that engage in extra-pair mating suggests that female and male participation in extra-pair behaviour may not share a common genetic basis as it does in zebra finches [56]. Alternatively, if female F 1 EPO are of higher quality, as indicated by their increased reproductive success, it may be the case that they are more likely to pair with preferred high-quality or compatible social males, and therefore would not gain an additional genetic benefit from mating with extra-pair males.…”
Section: Discussionmentioning
confidence: 99%
“…don 2000; Pilastro et al 2003;Matessi et al 2009;Morales et al 2009). If females differ consistently in the number of EPO in their broods, and the quantity of EPO is associated with individual quality (Forstmeier et al 2011), then a misleading association with paternal care can result ( fig. 1D).…”
Section: The Problemmentioning
confidence: 99%